Organizational Communication Patterns in Implementing the Vision and Mission of the Bontang Sundanese Wargi Society in Bontang City - Anita Ardianty Nugget Oktavianoe (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
Organizational communication patterns in an organization are an important factor in the success of the organization. Good communication will produce good results to realize the vision and mission of the organization. This research aims to find out how communication is carried out from superiors to subordinates to empower the Sundanese community or members. This research is a qualitative research with interview, observation and documentation methods, using 6 informants from Paguyuban Wargi Sunda Bontang structurally selected to be interviewed. The results show that the communication patterns used by the Wargi Sunda Bontang Association in implementing its vision and mission are using Diagonal Communication Patterns, Horizontal Communication Patterns and Vertical Communication Patterns. The suggestion of this research is that Paguyuban Wargi Sunda Bontang Bontang City should be made an art certification as a legal umbrella in every activity carried out.